PdCl2(1-methylimidazole)2-catalysed Suzuki–Miyaura and Mizoroki–Heck Reactions Performed in Neat Water. (May 2013) - Li, Yao; Lin, Xiao-Fang; Liu, Meng-Yuan; Zhang, Lu-Lu; Jin, Ai-Ping; Lu, Jian-Mei
PdCl2 (1-methylimidazole)2 was an effective catalyst in neat water for the Suzuki–Miyaura and Mizoroki–Heck reactions of aryl bromides and iodides with, respectively, arylboronic acids and acrylic acid. Under optimal conditions, the products, variously substituted biphenyls and monosubstituted trans -cinnamic acids, respectively, were formed in good to almost quantitative yields.